2017
DOI: 10.1038/s41598-017-00698-4
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor, a novel proto-oncogene in non-small cell lung cancer, promotes tumor growth via directly transactivating CCND1

Abstract: Farnesoid X receptor (FXR), a nuclear receptor for maintaining bile acid homeostasis, has been recognized as a tumor suppressor in enterohepatic tissues. However, its expression and functional role in non-small cell lung cancer (NSCLC) remain unclear. We report that FXR is significantly increased in NSCLC and that it predicts poor clinical outcomes in NSCLC patients. FXR knockdown in NSCLC cells inhibited in vitro cell proliferation, blocked xenograft growth in nude mice, and delayed the G1/S transition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 37 publications
(45 reference statements)
1
26
0
1
Order By: Relevance
“…CCND1 has been postulated to play a potential oncogenic role in human cancers, including bladder cancer [34], estrogen receptor positive breast cancer [35] and prostate cancer [36]. Moreover, accumulating evidence has suggested that CCND1 has oncogenic potential in the development and progression of NSCLC [37][38][39]. In the present study, we firstly confirmed that CCND1 was a direct target of miR-342.…”
Section: Usa) Following the Manufactsupporting
confidence: 79%
“…CCND1 has been postulated to play a potential oncogenic role in human cancers, including bladder cancer [34], estrogen receptor positive breast cancer [35] and prostate cancer [36]. Moreover, accumulating evidence has suggested that CCND1 has oncogenic potential in the development and progression of NSCLC [37][38][39]. In the present study, we firstly confirmed that CCND1 was a direct target of miR-342.…”
Section: Usa) Following the Manufactsupporting
confidence: 79%
“…Moreover, our study demonstrated that knockdown of FXR in colon cancer cells induced EMT, accompanied by upregulation of Snail, Slug, vimentin, fibronectin, and MMP-9, and downregulation of E-cadherin and ZO-1, whereas ectopic expression of FXR had reversed change. In non-small-cell lung cancer, FXR functions as a proto-oncogene, promoting cell proliferation by directly transactivating cyclin D1 46 . In pancreatic cancer, increased FXR promotes cell invasive and migratory ability 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In breast carcinoma patients, the expression levels of FXR were positively correlated with tumor size and the proliferative rate of tumor cells [ 107 ], suggesting FXR as a prognosticator of invasive breast carcinoma. Consistently, the FXR expression was significantly increased in non-small cell lung cancer (NSCLC), which stimulated tumor growth through the direct transactivation of the cyclin D1 ( CCND1 ) gene [ 108 ]. Therefore, FXR may have pleiotropic effects on tumorigenesis, according to tissue types; FXR may primarily act as a tumor suppressor gene in enterohepatic tissues, but it can be a proto-oncogene in other tissues, including breast and lung.…”
Section: Biological Roles Of Fxr In Various Organs and The Inter-omentioning
confidence: 99%